A rare case of Mullerian agenesis with descent of gonads - Tripathy, Saswati; Chandrasekhar, Anjalakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Presence of ovary in inguinal hernia is a rare condition. The diagnosis is made either radiologically or laparoscopically. We report a case of primary amenorrhoea with ovarian inguinal hernia. Psychological support should be provided as a part of management.